The Effect of Education on Economic Growth in Sub-Saharan African Countries: Do Institutions Matter? - Mohammed N. Abu Alfoul; Ayman Hassan Bazhair; Ibrahim N. Khatatbeh; Adam G. Arian; Mahmoud N. Abu Al-Foul (Economies)
This paper investigates the moderating role of institutional quality on the relationship between education and economic growth in Sub-Saharan Africa (SSA). The study applies the panel ARDL model to data from 18 SSA countries spanning 2000–2020 for its main analysis, along with a battery of diagnostics test to ensure the robustness of the results. The results reveal that the long-term effect of education on economic growth is statistically insignificant, attributing this finding to high rates of education exclusion and low-quality education. Remarkably, the research emphasizes the moderating role of institutional quality, showing the positive effects of education on economic growth when countries demonstrate robust corruption control and political stability. The study contributes to the existing literature by highlighting specific institutional factors influencing the effectiveness of education in driving economic growth, emphasizing the need for a strong institutional framework alongside educational efforts for sustainable development. The findings highlight that robust institutions form a crucial infrastructure that enhances the effectiveness of education in driving productivity and fostering economic growth.